An analysis of the translated works produced by transtool computer program - Gunawan, Gunawan (2006)
The software company creates various software of computer which can assist all translators and translation agents. One of those programs is TransTool. This study analyzes the translated works produced by TransTool computer Program. The objectives of the study are to know the accuracy of translating English into Indonesian by using TransTool program and to know the strength and weakness of TransTool program. In this study, the researcher uses two kinds of data sources, primary and secondary data sources. The primary data source is translated text produced by TransTool and the object of the study is TransTool computer program, while the secondary one is text taken from books, translation journal, and article related to translation. The data is collected through documentation and analyzed by comparing between SL and TL. Based on the analysis, the researcher draws some conclusions as follows: (1) TransTool is not quite accurate in translating short text. From 40 datum, it is only 55 % or 22 datum is considered accurate. It is, even, worse when TransTool translating long text. The translated material is not coherent and there are too many mistakes. From 3 data, it is only 0 % or 0 datum is considered accurate; (2) the strengths of TransTool are to help the translator to find difficult word, so the translator does not have to open the dictionary to find the difficult word and it will save the time. Beside that, TransTool can translate simple sentences accurately; and (3) TransTool has the weaknesses, they are: TransTool does not understand the culture dimension of the languages, it does not have good intuition and also it does not understand the objective of translation, last but not least, TransTool cannot translate correctly in complex sentences.